Investigation on the accessibility in transportation hubs: upgrades in London - Abdul Rahim, Asiah; Zen, Ismawi; Abd. Samad, Nur Amirah; Che Rahim, Che Raiskandar; Badhrulhisham, Aiman (2014)
A study to investigate Universal Design applications in selected transportation hub in London that has undergone upgrades and transformations to provide more accessibility for its commuters. Public transportation is one of the most important facilities in an urban area, London has a long history of transportation network in providing access to central London and its greater suburbs areas to allow smooth and easy alternative to move from one place to another besides personal cars. Kuala Lumpur, Tokyo and London are examples of major cities that rely heavily on railway transportation system, especially for domestic logistics. It is only logical then, that stations and hubs for these transportation systems be accessible for all types of users, including the disabled and the aged. Denying them access to these facilities will greatly affect their lives, considering how important railway system is these days. This study will evaluate the application of Universal Design in London transportation hub stations to learn the possibilities and hurdles in creating accessible hubs as a benchmark for Kuala Lumpur’s accessibility design consideration. Transportation hubs and train stations in Malaysia varies according to its era built and variation of transit systems. Standard construction drawings prevent major layout changes and many authority constrains regarding older designs are restricted in many aspect to provide accessible layouts.